Leaf wax n-alkane distribution and hydrogen isotopic fractionation in fen plant communities of two Mediterranean wetlands (Tenaghi Philippon, Nisí fen—Greece) - Ardenghi, Nicolò; Mulch, Andreas; McFarlin, Jamie M.; Sachse, Dirk; Kahmen, Ansgar; Niedermeyer, Eva M. (Frontiers in Earth Science, 2024)
Many continental paleoclimate archives originate from wetland sedimentary sequences. While several studies have investigated biomarkers derived from peat-generating vegetation typical of temperate/boreal bogs (e.g., Sphagnum), only scant information is available on emergent plants predominant in temperate/subtropical coastal marshlands, peri-lacustrine and fen environments. Here, we address this gap, focusing on two wetlands in the Mediterranean (Nisí fen and Tenaghi Philippon, Greece). We examined the concentration, homologue distribution, and hydrogen stable isotopic composition (δ2H) of leaf wax n-alkanes in 13 fen plant species, their surrounding soil, and surface water during the wet growing season (spring) and the declining water table period (summer). Our findings indicate that local graminoid species primarily contribute to the soil n-alkane signal, with a lesser influence from forbs, likely owing to differences in morphology and vegetation structure. The δ2H values of surface and soil water align with local average annual precipitation δ2H, reflecting winter-spring precipitation. Consistently, the average δ2H of local surface, soil, and lower stem water showed negligible evaporative enrichment, confirming minimal 2H-fractionation during water uptake. We find that δ2H values of source water for wax compound synthesis in local fen plants accurately mirror local annual precipitation. Furthermore, despite differences between leaves and lower stems in n-alkane production rates, their δ2H values exhibit remarkable similarity, indicating a shared metabolic substrate, likely originating in leaves. Our net 2H-fractionation values (i.e., precipitation to leaf n-alkanes) align with those in Chinese highlands and other similar environments, suggesting consistency across diverse climatic zones. Notably, our data reveal a seasonal decrease in the carbon preference index (CPI) in plant samples, indicating wax lipid synthesis changes associated with increased aridity. Additionally, we introduce a new parity isotopic difference index (PID) based on the consistent δ2H difference between odd and even n-alkane homologues. The PID demonstrates a strong anticorrelation with plant CPI, suggesting a potential avenue to trace long-term aridity shifts through δ2H analysis of odd and even n-alkane homologues in sedimentary archives. While further development of the PID is necessary for broad application, these findings highlight the intricate interplay between plant physiology, environmental parameters, and sedimentary n-alkanes in unravelling past climatic conditions.